Identification and analysis of cation channel homologues in human pathogenic fungi. - David L Prole (Public Library of Science (PLoS), 2012)
Fungi are major causes of human, animal and plant disease. Human fungal infections can be fatal, but there are limited options for therapy, and resistance to commonly used anti-fungal drugs is widespread. The genomes of many fungi have recently been sequenced, allowing identification of proteins that may become targets for novel therapies. We examined the genomes of human fungal pathogens for genes encoding homologues of cation channels, which are prominent drug targets. Many of the fungal genomes examined contain genes encoding homologues of potassium (K(+)), calcium (Ca(2+)) and transient receptor potential (Trp) channels, but not sodium (Na(+)) channels or ligand-gated channels. Some fungal genomes contain multiple genes encoding homologues of K(+) and Trp channel subunits, and genes encoding novel homologues of voltage-gated K(v) channel subunits are found in Cryptococcus spp. Only a single gene encoding a homologue of a plasma membrane Ca(2+) channel was identified in the genome of each pathogenic fungus examined. These homologues are similar to the Cch1 Ca(2+) channel of Saccharomyces cerevisiae. The genomes of Aspergillus spp. and Cryptococcus spp., but not those of S. cerevisiae or the other pathogenic fungi examined, also encode homologues of the mitochondrial Ca(2+) uniporter (MCU). In contrast to humans, which express many K(+), Ca(2+) and Trp channels, the genomes of pathogenic fungi encode only very small numbers of K(+), Ca(2+) and Trp channel homologues. Furthermore, the sequences of fungal K(+), Ca(2+), Trp and MCU channels differ from those of human channels in regions that suggest differences in regulation and susceptibility to drugs.